Public Values Program Santunan Kematian Bagi Masyarakat Miskin di Kabupaten Bojonegoro - Handayani, Putri; Suprastiyo, Ahmad; Suhindarno, Heny (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research aims to explain the public value of the poor death compensation program in Bojonegoro Regency as perceived by the general public. The Death Compensation Program for the Poor in Bojonegoro Regency is designed to provide assistance to poor heirs whose family members have died as a manifestation of the concern of the Bojonegoro Regency Government. This research uses Mark Moore's public value theory, Legitimacy and Support, Operational Skills, and Substantial Value. This research uses a descriptive method with a qualitative approach. In this study, a purposive sampling strategy was used to identify informants. Through research it is known that the Death Compensation Program for the Poor in Bojonegoro Regency has received support from the community, from an operational capability perspective supported by quality human resources, technology and finance. In terms of substantial value, it has benefits from economic value, social and social value, and political value. Although there are still several obstacles, especially in terms of data filling by the public and telecommunications networks.